2019
DOI: 10.1111/liv.14213
|View full text |Cite
|
Sign up to set email alerts
|

Procoagulant imbalance influences cardiovascular and liver damage in chronic hepatitis C independently of steatosis

Abstract: Background & Aims:Patients with chronic HCV infection besides hepatitis often present cardiovascular damage, the pathogenesis of which is not defined. In chronic liver diseases, including NAFLD and cirrhosis, a procoagulant imbalance, potentially responsible for atherosclerosis has been reported. We aimed at evaluating whether a procoagulant imbalance is present also in non-cirrhotic patients with HCV infection and whether the procoagulant imbalance correlates with cardiovascular damage.The correlation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Similarly, liver fibrosis, but not steatosis, was associated with a procoagulant imbalance in chronic hepatitis C patients. 28 However, we could not assess and draw conclusions on the regulation of fibrinolysis, which in a recent study was found impaired in non-diabetic patients with NAFLD, 29 and on the role of neutrophil extracellular traps in triggering coagulation in participants with liver inflammation. 30 Notwithstanding, the present results seem to confirm that subclinical systemic inflammation (CRP levels) impact on the coagulation balance at different levels, 31 even in this cohort of apparently healthy and asymptomatic individuals, but most importantly showed that the association of early liver damage with procoagulant imbalance is independent of CRP.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, liver fibrosis, but not steatosis, was associated with a procoagulant imbalance in chronic hepatitis C patients. 28 However, we could not assess and draw conclusions on the regulation of fibrinolysis, which in a recent study was found impaired in non-diabetic patients with NAFLD, 29 and on the role of neutrophil extracellular traps in triggering coagulation in participants with liver inflammation. 30 Notwithstanding, the present results seem to confirm that subclinical systemic inflammation (CRP levels) impact on the coagulation balance at different levels, 31 even in this cohort of apparently healthy and asymptomatic individuals, but most importantly showed that the association of early liver damage with procoagulant imbalance is independent of CRP.…”
Section: Discussionmentioning
confidence: 92%
“…Since slow portal blood flow is a major risk factor for the development of PVT, 2 this might partly explain the low incidence of PVT in our cohort. Virological cure might lead to an improvement in HCV‐associated hyper‐coagulability 13,14,36 and a decrease in the thrombotic tendency associated with cirrhosis 37 . Patients with more advanced liver disease in whom SVR seems not to be associated with a significant reversal of coagulopathy 13 would remain at risk of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…And we found that LFS could predict thrombotic events in ACS patients but not bleeding events. Procoagulant imbalance is common in people with chronic liver disease, even those with mildly elevated liver fibrosis scores [ 33 ]. Inflammatory status, elevated thrombophilic factors, endothelial dysfunction, and oxidative injury in liver fibrosis or cirrhosis lead to hypercoagulable and thrombotic state [ 34 , 35 ], increasing ischemic events risk.…”
Section: Discussionmentioning
confidence: 99%